Parental Understanding of Safe Internet Access for Early Childhood - Ellen Prima; Dewi Ariyani; Ratna Widiati Dwi Kartika; Handini Nindya Anggita; Sania Agus Winanda (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This study examines parental comprehension regarding safe internet access using a qualitative descriptive approach. Participants included parents of early childhood students from various state kindergartens in Purwokerto: West Purwokerto, South Purwokerto, East Purwokerto, and North Purwokerto. Data collection encompassed stages of data collection, reduction, categorization, presentation, and verification. Findings revealed that parents' understanding of safe internet access primarily focused on digital utilization. This level of understanding was achieved through diverse avenues, including educational counseling and parenting activities conducted within schools. Parents demonstrated their preference for educational websites and applications as learning resources, and facilitated online learning by providing internet-enabled devices. Furthermore, parents reinforced internet access governance by establishing rules and agreements governing gadget and internet use. This governance was further supported through ongoing monitoring while children engaged with devices, both during and outside of learning contexts.